BASIC METHODS OF TRAINING OF OFFICIAL DOGS - Pustova , N.V.; Shuplyk, V.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Training of official dogs takes place in a result from the action of certain methods, methodologies, receptions and complex of methods on the organism of dog from early age and in particular on the nervous system, that together with the inherited signs forms for the puppy-dog of basis of activity of the nervous system on necessary to the trainer internalss and skills. The aim of our researches was to define the basic methods of training of official dogs in the cynologistic center of the Khmelnytsk area. Due to a selection and selection a man formed desirable internalss at the different breeds of dogs, sometimes nature strengthened properties of certain orientation, for today to the basic breeds of official dogs belong: the German, Caucasian and Belgian shepherds, doberman, rottweiler and other. During researches studied the purchased experience of the use of the marked breeds of official dogs at implementation by them such tasks: to the search and watching, being of explosive, drugs, weapon and others like that. Analysing the got results of implementation of tasks the different breeds of official dogs (in accompaniment with a cynologist) it was educed that taking into account genetic potential and individual features of every animal determine an official dog will work in what direction. The methods of training of dogs in a cynologistic center apply such: mechanical, encouraging, contrasting, inheritance. Taking into account the different methods of training of official dogs in their basis, making of pavlovian reflexes lies on certain irritants, however in basis of training there is encouragement (delicious, by a toy, stroking, and others like that) : did right - got a reward, wrong - got nothing. Training of official dogs conduct, in an order to produce the special skills for a dog. Not depending on a breed official dogs are able to watch and detain criminals, find a weapon, explosive and drugs, search disappearing people and much what. Direction an official dog will work after that is determined by his nature and temperament.